Dental Suction Aerosol: Bibliometric Analysis - Doni Fajar Ramadhan; Azhar Muhammad Fabian; Hendri Maja Saputra (Universitas Pendidikan Indonesia (UPI), 2022)
The rapid spread of the coronavirus had a bad impact on many things, especially on the medical sector. Medical personnel especially dentists are one of the sectors most exposed to the coronavirus because dental procedures produce aerosols and splashes that are contaminated with saliva and blood. This study aimed to investigate the development of research related to dental aerosol suction through the distribution of bibliometrics maps and research trends using VOSViewer. Bibliometric mapping shows the types of publications, publication authors, and publishers of scientific articles. In this study, data collection was carried out from the dimensions.ai site which provides a dataset of scientific articles that have been published in international journals under open source. The keyword was